Pro Ajax and the .NET 2.0 Platform - Woolston, Daniel (Apress : Imprint: Apress, 2006)
There are a few class libraries recently distributed that open the Ajax door to the .NET Framework 2.0. This book examines how the Ajax technology and the .NET Framework can work in tandem. It thoroughly covers the XMLHttpRequest processes and the .NET 2.0 class libraries, and shows you how to turn theory into practice and concepts into code, with samples that duplicate many new web technologies. With the knowledge you gain from this book, you'll be ready to put this asynchronous technology to work. Thanks to the folks at Google, Ajax technology has become a force to be reckoned with. It is a technology that is here and now, just waiting for you to implement it with full impact. Google Maps, Google Suggest, and Flickr.com are just a few of the sites out there that have moved Ajax into the mainstream. More shall be revealed as the technology eases its way into coding.